2012
DOI: 10.1083/jcb.201108143
|View full text |Cite
|
Sign up to set email alerts
|

Hic-5 promotes invadopodia formation and invasion during TGF-β–induced epithelial–mesenchymal transition

Abstract: The focal adhesion protein Hic-5 acts through RhoC to promote TGF-β–stimulated invadopodia formation, cell migration, and invasion.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

11
136
1
6

Year Published

2013
2013
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 142 publications
(155 citation statements)
references
References 65 publications
11
136
1
6
Order By: Relevance
“…In MDA-MB-253 cells, Hic-5 depletion decreases the number of vinculin-positive focal adhesions and motility in 3D (Deakin and Turner, 2011). Although a specific proteinase was not identified, Hic-5 depletion has been connected to decreased matrix degradation and filopodia formation (Pignatelli et al, 2012). Wang and McNiven have previously implicated focal adhesions as sites for MT1-MMP-dependent matrix degradation in tumor cells (Wang and McNiven, 2012), and others have suggested the importance of MT1-MMP and focal adhesion crosstalk during cell migration (Wu et al, 2005b;Takino et al, 2006Takino et al, , 2007Gingras et al, 2008).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In MDA-MB-253 cells, Hic-5 depletion decreases the number of vinculin-positive focal adhesions and motility in 3D (Deakin and Turner, 2011). Although a specific proteinase was not identified, Hic-5 depletion has been connected to decreased matrix degradation and filopodia formation (Pignatelli et al, 2012). Wang and McNiven have previously implicated focal adhesions as sites for MT1-MMP-dependent matrix degradation in tumor cells (Wang and McNiven, 2012), and others have suggested the importance of MT1-MMP and focal adhesion crosstalk during cell migration (Wu et al, 2005b;Takino et al, 2006Takino et al, , 2007Gingras et al, 2008).…”
Section: Discussionmentioning
confidence: 99%
“…Hic-5 localizes to pseudopodia in bovine pulmonary artery endothelial cells (Avraamides et al, 2007) and invadopodia of breast cancer cells (Pignatelli et al, 2012). Studies in breast cancer cells have revealed that Hic-5 silencing attenuates integrin-mediated adhesion, migration, invasion and tumor cell metastasis (Deakin et al, 2012), and causes defective matrix degradation (Pignatelli et al, 2012).…”
Section: Introductionmentioning
confidence: 99%
“…68 Hic-5, a member of the paxillin family, localizes to invadopodia rings, and upon TGFβ stimulation, promotes ECM degradation in a src phosphorylation-dependent manner. 134 The role of Focal Adhesion Kinase in invadopodia regulation is rather controversial; it was shown to function as a negative regulator of invadopodia through the spatial control of src in MTLn3 mammary adenocarcinoma cells, 143 While other reports indicate that it is localized to invadopodia, and its increased expression promotes the formation of src-induced invadopodia. 144 VASP, another adhesome component, accumulates at the degradation sites of invadopodia in MDA-231 breast cancer cells 83 and its phosphorylation on Ser239 was reported to suppress invadopodia formation, and inhibit the formation of cancer metastasis.…”
Section: The Invasive Domainmentioning
confidence: 99%
“…3,4 It is noteworthy that podosomes, have typical lifetimes on the order of a few minutes, while invadopodia can be stable for hours. 1 More recently, these claims were challenged by the detection of vinculin, paxillin, and Hic-5 in rings located at the periphery of newly formed invadopodia in various cultured cancer cell lines 52,134 (and our unpublished data Fig. 2).…”
Section: The Invasive Domainmentioning
confidence: 99%
“…To better characterize the effects of EMT inducers on PYK2 expression, we assessed its protein level in MCF10A and MDA-MB-468 cells in response to two potent EMT inducers: TGFb and EGF. The immortal mammary human epithelial MCF10A cells undergo EMT in response to EGF or TGFb 29 , whereas MDA-MB-468 cells, an invasive human breast carcinoma, undergo EMT in response to EGF 30 . As shown in Fig.…”
Section: Elevated Pyk2 Expression Enhances Emt In Mammary Cellsmentioning
confidence: 99%